Major opinion about motherhood among women with Turner syndrome - Malgorzata Wiecek; Wiktoria Kempinska; Aneta Gawlik-Starzyk (Ginekologia Polska)
OBJECTIVES: Turner syndrome (TS) is associated with ovarian dysgenesis leading to infertility in most of the cases. There are some options for fertility preservation (FP) in patients with sufficient follicle numbers. The most recently studied are oocyte and ovarian tissue preservation. Due to premature ovarian failure among TS girls, the procedure should be performed as early as possible. The aim of this study is to gain the opinions of women with TS about motherhood based on the web-survey. MATERIAL AND METHODS: The survey, hosted on SurveyMonkey.com, targeted women over 18 years with TS. It comprised 16 single-choice questions, ensuring anonymity and consent for data usage. RESULTS: The answers of a total of 152 women were analyzed. When asked if they had discussed motherhood options with their physicians, 72/152 of the participants responded negatively. Asked about the desire of maternity, 85/152 expressed a desire to have children. 5/152 had biological children from spontaneous pregnancies, 5/152 had biological children through oocyte donation, 1/152 through embryo donation, and 12/152 had adopted children. 75/150 respondents answered yes to the question of whether they desired to use ovarian tissues if they had been preserved during adolescence. CONCLUSIONS: The findings suggest that a significant number of women with TS who aspire to become mothers would be inclined to use preserved cells if this option were available. This underscores the necessity for further exploration of FP techniques for individuals with TS.